Conceptualising Internet of Things and Artificial Intelligence Enabled Smart Homes (Journal of Pharmaceutical Negative Results, 2022)
“Can machines think?” Alan Turing (1950). The answer is yes. Today machines have ability to understand, process external inputs, learnfrom these inputs and use those inputs to achieve specific goal or task. Since 1956, when the term “Artificial Intelligence” was coined first by John McCarthy and Marvin Minsky, the world has made significant progress in the field of Artificial Intelligence (AI). It is being used to solve various problems either beyond human control or difficult for humans to solve. It has disrupted business operations, health infrastructure, entertainment and above all the human experience. Machines can be equipped with ability not only to learn and apply but also to interact with other machines and get a task completed. Development in IT and telecom infrastructure has facilitated this interaction between the machines which is called Internet of Things (IoT). AI and IoT is being used together to solve critical aspects of human life. Smart home built with AI and IoT will make human life more convenient and simple. However, the concept of smart home is still in nascent stage and has not been completely developed. Various authors and researchers discussed services provided by smart homes but no researcher came up with comprehensive list of services that a smart home can offer. Also, role of artificial intelligence has been neglected by almost all researchers.Objective of this study is to understand and define Smart Homes comprehensively. This study is focused on studying previous literatures and available technologies that can be used to make a full-fledged smart home providing all services possible in current technological environment. This research is mainly focused on analysing research papers and articles published recently. Qualitative research tool is usedto analyse the literature.